2022
DOI: 10.1186/s41601-022-00261-y
|View full text |Cite
|
Sign up to set email alerts
|

Online estimation of SOH for lithium-ion battery based on SSA-Elman neural network

Abstract: The estimation of state of health (SOH) of a lithium-ion battery (LIB) is of great significance to system safety and economic development. This paper proposes a SOH estimation method based on the SSA-Elman model for the first time. To improve the correlation rates between features and battery capacity, a method combining median absolute deviation filtering and Savitzky–Golay filtering is proposed to process the data. Based on the aging characteristics of the LIB, five features with correlation rates above 0.99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…With the development of economy, science, and technology, today’s society has entered a highly developed intelligent era. In the process of the new technological revolution, signal sensing is a key link and an important technical element. As an important information acquisition tool, sensors play a very important role in signal transmission in different sensing fields. In real life, sensors with various functions are similar to various organs of the human body and they are all indispensable parts for sensing external stimuli. At present, the research of robot is a very important field in the intelligent era and numerous research groups have done a lot of research on robot’s autonomous behavior, remote observation, and interaction ability in special environment. In order to perceive the behavior state in different working conditions, it is necessary to improve the sensing ability of the robot to adapt to the signal perception in more complex environments. …”
Section: Introductionmentioning
confidence: 99%
“…With the development of economy, science, and technology, today’s society has entered a highly developed intelligent era. In the process of the new technological revolution, signal sensing is a key link and an important technical element. As an important information acquisition tool, sensors play a very important role in signal transmission in different sensing fields. In real life, sensors with various functions are similar to various organs of the human body and they are all indispensable parts for sensing external stimuli. At present, the research of robot is a very important field in the intelligent era and numerous research groups have done a lot of research on robot’s autonomous behavior, remote observation, and interaction ability in special environment. In order to perceive the behavior state in different working conditions, it is necessary to improve the sensing ability of the robot to adapt to the signal perception in more complex environments. …”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, how to solve the problem of zinc dendrite growth is an important challenge. 11 In order to solve this challenge of obtaining highperformance zinc anodes, the research procedure mainly involves the following ways to improve the performance of zinc anodes, (i) covering the zinc surface with a protective layer, [12][13][14] (ii) adjusting the structure of the electrolyte, [15][16][17] and (iii) changing the metal structure of the zinc anode. [18][19][20] Recently, it has been reported that creating a copper-zinc alloy material on the zinc surface inhibits the electrochemical corrosion of aqueous zinc metal and improves the cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…The rise of electric vehicles around the world is driving the search for batteries with low cost and high energy density. In existing commercial lithium-ion batteries, the anode has made great progress, while the main bottleneck at present is the mismatched and insufficient capacity of the cathode . Li-rich Mn-based layered oxides (LLOs) are considered one of the most promising cathode materials because their capacity exceeds 250 mA h/g. , The redox reaction of transition metal ions (TM n + /TM ( n +1)+ ) and anions (O 2– /O 2 ) is the primary reason for LLOs’ remarkable capacity.…”
Section: Introductionmentioning
confidence: 99%